177k views
4 votes
Hello! can anyone help me with this question

Hello! can anyone help me with this question-example-1
User Kalenda
by
5.1k points

2 Answers

5 votes

hi there

the explanation is in the picture

Hello! can anyone help me with this question-example-1
User Maksym Gontar
by
5.2k points
1 vote

Answer:

3

Explanation:

m = y2 - y1 / X2 - X1

-1 is your X1 . -4 is your y1

2 is your X2 . 5 is your y2

just replace what's in the equation

m= 5 - (-4) / 2 - (-1)

m= 9 / 3

m = 3

User Abdallah Sakre
by
5.1k points